A digital iCBT intervention for social anxiety disorder in Quebec and Ontario: protocol for a multi-phase effectiveness-implementation study - Vasiliadis, Helen-Maria; Roberge, Pasquale; Spagnolo, Jessica; Lamoureux-Lamarche, Catherine; Chapdelaine, Alexandra; Brodeur, Magaly; Grenier, Jean; Mahoney, Alison; Koszycki, Diana; Chomienne, Marie-Hélène; Drapeau, Martin; Labelle, Réal; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Social anxiety disorder (SAD) is one of the most prevalent anxiety disorders in Canada. Viable therapy options for the treatment of SAD include CBT being delivered virtually. In Australia, an innovative internet-delivered cognitive-behavioral therapy (iCBT) program for social anxiety has been developed, implemented, and demonstrated as effective. To make available high-quality and real-time evidence in response to the crucial need to access psychological services to meet population mental health needs, we propose to conduct a Canadian adaptation of the iCBT Shyness Program and to examine the program’s effectiveness, and implementation in two Canadian provinces (Quebec and Ontario). Methods The overall study design is a hybrid effectiveness-implementation study of a quasi-experimental parallel group trial. Prior to implementing the iCBT Shyness Program, it will undergo an initial adaptation to the Canadian context and focus groups will be conducted with key actor groups to discuss the adaptations to the graphics, narration of the lessons, and this to better reflect varying socio-cultural context among Canadian French- and English-speaking populations. We will evaluate the effectiveness of the program in three parallel pathways reflecting real-world pathways: (1) self-refer to the intervention; (2) recommended by a health professional without guidance; and (3) recommended by a health professional, with low-intensity guidance. Data collection will be carried out at baseline, at the beginning of each lesson, 12-week and 6-month follow-up. Outcomes measured will include anxiety and depressive symptoms, psychological distress, disability, as well as health service utilization and satisfaction. Semi-structured interviews will then be conducted with study participants and health care providers to explore facilitating factors and barriers to the implementation of the iCBT adapted program. Discussion This study will provide evidence on the effectiveness, barriers and facilitating factors to implementing a low-intensity iCBT in the Canadian context for SAD, which will bridge an important care gap for undeserved populations in Canada with SAD. Findings will inform the eventual scaling up of the program in community-based primary care across Canada. This would improve equity of the health care system by helping a large number of Canadians to timely access to mental health services. Trial registration clinicaltrials.gov NCT06403995. Prospectively registered on 05/03/2024.